Spatio-temporal maneuvering of impacting drops. Issue 11 (27th September 2021) - Han, Xing; Tang, Xin; Zhao, Haibo; Li, Wei; Li, Jiaqian; Wang, Liqiu
Abstract : Spatio-temporal control of impacting drops can be achieved by a combination of a nonwetting fin and a wetting stripe on a nonwetting surface. Abstract : Controlling impacting drops on nonwetting surfaces is desired in multifarious processes. Efforts have been made to solely spatially control the drop movement after the impact or solely temporally reduce liquid–solid contact via surface design. We present a fin–stripe nonwetting surface that enables spatial offset maximization and temporal contact minimization simultaneously, just via structure design without the need for external energies. The wetting stripe provides a large wettability gradient for lateral movement, while the macroscale nonwetting fin restricts the drop movement direction and confines drop spreading for contact time reduction. The fin–stripe surface can decrease the contact time by roughly 30% and provide a normalized lateral distance of roughly 20, an order of magnitude larger than the reported values. Our surface enables effective spatio-temporal maneuvering of impacting drops, essential for various applications that involve liquid transport.